CONTRIBUCIÓN AL CONOCIMIENTO DE LOS ODONATAZYGOPTERA DE COLOMBIA: LOS ADULTOS DE Enallagma civile (HAGEN) Y Cyanallagma lateralle (SELYS) (ODONATA: COENAGRIONIDAE) (2013)
Enallagma civile (Hagen, 1861) and Cyanallagma laterale (Selys, 1876) are described and ilustrated One rrwrphological close relation are observed between Cyanallagma laterale (selys) and Cyanallagma dernarrnelsi Cruz, shown in thejorm ojthe abdominal lo be ojprothorax, color ojthe abdominal segments and the apex ojpenijorm.